2012
DOI: 10.7150/jca.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Progression-free Survival Decreases with Each Subsequent Therapy in Patients Presenting for Phase I Clinical Trials

Abstract: Background: There is often a finite progression-free interval of time between one systemic therapy and the next when treating patients with advanced cancer. While it appears that progression-free survival (PFS) between systemic therapies tends to get shorter for a number of factors, there has not been a formal evaluation of diverse tumor types in an advanced cancer population treated with commercially-available systemic therapies.Methods: In an attempt to clarify the relationship between PFS between subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 70 publications
0
23
1
Order By: Relevance
“…Previous reports of studies of phase I trials of patients with gynecologic cancers receiving targeted therapies have shown that PFS is either shorter or, in some cases, comparable to the PFS duration achieved on prior conventional therapies [48, 49]. However, in the present study 26% of patients receiving MTB-based therapy experienced PFS durations similar to or longer than those experienced on prior therapy; some of these were ongoing.…”
Section: Discussioncontrasting
confidence: 49%
“…Previous reports of studies of phase I trials of patients with gynecologic cancers receiving targeted therapies have shown that PFS is either shorter or, in some cases, comparable to the PFS duration achieved on prior conventional therapies [48, 49]. However, in the present study 26% of patients receiving MTB-based therapy experienced PFS durations similar to or longer than those experienced on prior therapy; some of these were ongoing.…”
Section: Discussioncontrasting
confidence: 49%
“…When patients are treated with platinum-based therapies, consideration of these times leads to the designation of patients as platinum sensitive, resistant or refractory [9]; this status is believed to be correlated with future response to platinum therapy. Noting that, in advanced cancers, the TFI decreases in subsequent treatments for patients treated serially with systemic therapies [10], response to platinum is expected to decay, perhaps due to drug selection forces [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Compared with patients who have other solid tumors, patients with MBC have a larger number of therapeutic options available. 17 The likelihood of response and prolonged tumor control is highest with the first line of chemotherapy, with limited data on the efficacy of later lines of chemotherapy despite its very common use in clinical practice. [18][19][20] Few data also ex-ist regarding the impact of tumor subtype on the likelihood of benefit with later lines of treatment.…”
Section: Introductionmentioning
confidence: 99%